‘g' by Dropping Method - Verma, Manohar Lal (SCHOOL SCIENCE, 2018)
I have provided two methods for finding the value of ‘g’ (acceleration due to gravity). Both of these are my original ones. One is based on the principle of projectile(Verma, M.L.,2015) and other on the free dropping of bullet from height 1.23 m.